2010
DOI: 10.1007/s11557-010-0699-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and phylogeny of Hyaloperonospora erophilae and H. praecox sp. nov., two downy mildew species co-occurring on Draba verna sensu lato

Abstract: Based on morphological and molecular data, it is shown that two distinct Hyaloperonospora species parasitize Draba (syn. Erophila) verna sensu lato. Hyaloperonospora praecox is described and illustrated as a new species, and detailed descriptions and illustrations including the diagnostic disease symptoms, haustoria and oogonia are provided for H. erophilae for the first time. Based on morphological and ITS sequence data, Peronospora drabae-majusculae is synonymised with H. erophilae. Hyaloperonospora praecox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Additionally, this study revealed some previously unnoticed, host-specific lineages of Peronospora and that the type species of this genus is likely restricted to R. acetosella . These results support the view that a narrow species concept reflects the evolutionary history of downy mildews much better than a broad species concept, which is in line with recent studies for other species complexes, such as Bremia lactucae (Voglmayr et al, 2004; Choi et al, 2007b, 2011c), Hyaloperonospora parasitica (Choi et al, 2003, 2011b; Göker et al, 2004, 2009; Voglmayr and Göker, 2011; Voglmayr et al, 2014a), Peronospora arborescens (Voglmayr et al, 2014b), Peronospora lamii (Belbahri et al, 2005; Choi et al, 2009c; Thines et al, 2009b), and Plasmopara halstedii (Spring et al, 2003; Komjáti et al, 2007; Choi et al, 2009a).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, this study revealed some previously unnoticed, host-specific lineages of Peronospora and that the type species of this genus is likely restricted to R. acetosella . These results support the view that a narrow species concept reflects the evolutionary history of downy mildews much better than a broad species concept, which is in line with recent studies for other species complexes, such as Bremia lactucae (Voglmayr et al, 2004; Choi et al, 2007b, 2011c), Hyaloperonospora parasitica (Choi et al, 2003, 2011b; Göker et al, 2004, 2009; Voglmayr and Göker, 2011; Voglmayr et al, 2014a), Peronospora arborescens (Voglmayr et al, 2014b), Peronospora lamii (Belbahri et al, 2005; Choi et al, 2009c; Thines et al, 2009b), and Plasmopara halstedii (Spring et al, 2003; Komjáti et al, 2007; Choi et al, 2009a).…”
Section: Discussionsupporting
confidence: 91%
“…Recent molecular phylogenetic studies showed that the genus Hyaloperonospora , established by Constantinescu and Fatehi ( 2002 ) for Peronospora species infecting Brassicaceae , Capparaceae , Cistaceae , Limnanthaceae , Resedaceae and Zygophyllaceae , comprises a high biodiversity, its species usually being highly host specific (e.g. Riethmüller et al 2002 ; Choi et al 2003 ; Voglmayr 2003 ; Göker et al 2003 , 2004 , 2009a ; Choi et al 2011 ; Voglmayr and Göker 2011 ). Therefore, a narrow species circumscription as already advocated by Gäumann ( 1918 , 1923 ) has been confirmed, disproving the widely applied concept of Yerkes and Shaw ( 1959 ), who classified all accessions from Brassicaceae under a single species, H. parasitica (see review in Voglmayr 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…exhibits a high degree of differentiation according to the host species [14]. In addition, it adds evidence to the recently re-appraised view that a narrow species concept reflects the evolutionary history of downy mildews much better than a broad species concept, as exemplified on other species complexes, such as the ones around Bremia lactucae [35][36][37][38][39][40][41], Hyaloperonospora parasitica [42][43][44][45][46][47][48], Peronospora farinosa [7][8][9]49], Peronospora lamii [12,13,50], and Plasmopara halstedii [24,26,[51][52][53]. The downy mildew of I. textori is one of the most common downy mildew diseases throughout South Korea [21] and is common in China [54,55] and Japan [56] where the host plant is also widely distributed.…”
Section: Discussionmentioning
confidence: 83%